Teaching practitioners in the MBKM program: Enhancing students' learning outcomes in the AMDAL course - Nur Efendi; Noly Shofiyah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The Teaching Practitioner program is a key component of the Merdeka Belajar Kampus Merdeka (MBKM/Independent Learning Independent Campus) policy, a new educational initiative in Indonesia. This program aims to enhance graduates' competencies, including hard and soft skills, to strengthen their competitiveness in the era of globalization. Through this program, industry practitioners collaborate with lecturers to teach students in joint classes, providing real-world perspectives. This study aims to explore the role of teaching practitioners in improving students’ learning outcomes in the AMDAL (Analisis Mengenai Dampak Lingkungan Hidup/Environmental Impact Analysis) course, using a descriptive qualitative approach. The results indicate that the students’ mastery index (P = 0.86 ≥ 0.85) and classical mastery index (P = 1.00 ≥ 0.85) both meet the “good” category, demonstrating academic achievement. Additionally, students’ learning interest (mean = 3.58) and motivation (mean = 3.84) also fall into the “good” category. These findings suggest that teaching practitioners effectively improve students' academic performance, learning interest, and motivation. Therefore, this program should be continuously supported and expanded to sustain educational quality and produce graduates with strong expertise in various fields, especially those related to science and environmental studies.